IMPLEMENTASI KEGIATAN MENEMPEL UNTUK MENINGKATKAN MOTORIK HALUS SISWA DI SEKOLAH DASAR - Elisasmita; Farida Mayar; Desyandri (STKIP Subang, 2023)
This study aims to describe how sticking activities can improve fine motor skills in elementary school students. The research subjects were 4th grade elementary school students, with a total of 21 children consisting of 11 boys and 10 girls. Data collection techniques are carried out through observation and documentation. The instrument used is the observation sheet. The indicator of success in this study was the percentage calculation showing that 84% of children experienced an increase in fine motor skills through sticking activities with leaves as media. The results showed that children's fine motor skills increased after the action through sticking activities with leaves as media. When the pre-action was carried out, the percentage of children's fine motor skills increased by 28% to 59% in cycle I, and increased to 89% in cycle 2. It can be concluded that sticking activities with leaf media can improve the physical motor skills of elementary school students.